2019
DOI: 10.1002/adma.201807747
|View full text |Cite
|
Sign up to set email alerts
|

Living Materials Herald a New Era in Soft Robotics

Abstract: Living beings have an unsurpassed range of ways to manipulate objects and interact with them. They can make autonomous decisions and can heal themselves. So far, a conventional robot cannot mimic this complexity even remotely. Classical robots are often used to help with lifting and gripping and thus to alleviate the effects of menial tasks. Sensors can render robots responsive, and artificial intelligence aims at enabling autonomous responses. Inanimate soft robots are a step in this direction, but it will on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 213 publications
(376 reference statements)
0
76
0
Order By: Relevance
“…It has been demonstrated that microrobots have great potential for use in many applications, such as healthcare, bioengineering, and micromanipulation, [ 1–4 ] representing an increasingly significant research topic. In particular, soft microrobots made of deformable materials have captured the interest of a large number of researchers, [ 5–7 ] because their excellent soft and elastic properties enable the robots to achieve morphological transformation robotically. The deformability of soft microrobots makes them more manoeuvrable and gentler when interacting with surrounding objects; they also exhibit more interesting properties and have unparalleled advantages in comparison to rigid microrobots.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that microrobots have great potential for use in many applications, such as healthcare, bioengineering, and micromanipulation, [ 1–4 ] representing an increasingly significant research topic. In particular, soft microrobots made of deformable materials have captured the interest of a large number of researchers, [ 5–7 ] because their excellent soft and elastic properties enable the robots to achieve morphological transformation robotically. The deformability of soft microrobots makes them more manoeuvrable and gentler when interacting with surrounding objects; they also exhibit more interesting properties and have unparalleled advantages in comparison to rigid microrobots.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by such processes, engineered living materials (ELMs) employ the autonomy of living cells to synthesize and control material structures across multiple scales with user-designed functions that are directly coupled to gene expression (2)(3)(4)(5). Living materials containing microbes, including biofilms, bacterial cellulose, curli fibers, and synthetic gels loaded with bacteria, are of prominent interest due to their potential application in tissue engineering, 3D printing, soft robotics, metabolic engineering, and living sensors (6)(7)(8)(9)(10). Bacteria are particularly attractive as ELM components due to their natural sensing capabilities and programmability.…”
Section: Introductionmentioning
confidence: 99%
“…Even more, other features from biological tissues, such as self-healing, energy efficiency, power-to-weight ratio, adaptability or biosensing, are strongly desired but difficult to achieve with artificial soft materials [19] . Bio-hybrid robotics is born at this point as a synergistic strategy to integrate the best characteristics of biological entities and artificial materials into more efficient and complex systems that can overcome the difficulties that current soft robots face [20,21] . Therefore, the design of bio-hybrid robots relies on the combination of living cells/tissues with a synthetic material, and such living entities can range from individual motile cells at the microscale (i.e.…”
Section: Introductionmentioning
confidence: 99%